Bricks without straw - Priestland, Gerry; Smith, Martin W.; Alcott, Barrie (Watfold, Wd. Rank Foundation-CtVC production, 1988)
This program examines the plight of the homeless in London, Lusaka and Manila.
Keywords: Homelessness -- London; Homelessness -- Manila; Homelessness -- Northern Rhodesia